A Rapid Transition to Blended Learning: The Journey of a Dental Degree Programme Pivoting Online. (2021) - McKerlie, Robert Allen; Malcolm, Jennifer; Varsou, Ourania; Kennedy, Christopher Edward; Colgan, Laura; Harper, Victoria; McAllan, Wendy; Forgie, Andrew; Rea, Paul; Bell, Aileen
No abstract available